Modul "Safe Motherhood" Dalam Kurikulum Inti Pendidikan Dokter di Indonesia - SAIFUDDIN, Abdul bari ([Tidak Terdaftar], 1997)
Modul "Safe Motherhood" Dalam Kurikulum Inti Pendidikan Dokter di Indonesia